Facile preparation of activated carbon supported nano zero-valent iron for Cd(Ⅱ) removal in aqueous environment. (1st January 2023) - Cao, Xingfeng; Liu, Qiaojing; Yue, Tiantian; Zhang, Fengzhi; Liu, Liheng
Abstract: Activated carbon-supported nano-zero-valent iron (nZVI@AC) is considered to be one of the most promising materials for in-situ remediation of pollutants in aqueous environment, while liquid phase reduction (LPR) is one of the most commonly used preparation methods for nZVI@AC. However, the complex operation and the requirement of various agents limit the practical application of the traditional liquid-phase reduction (TLPR). In this study, an improved liquid phase reduction method (ILPR) was proposed, which was characterized by solid-state dosing of reducing agents. Compared with TLPR, ILPR simplified the preparation process, while there was no requirement of polyethylene glycol and ethanol. When the Cd(II) removal efficiency was used as the evaluation index, the preferred parameters of ILPR were as follows: AC/FeSO4 ·7H2 O mass ratio was 15:1; NaBH4 dosage was 8 g; ultrasonic time was 1 h; stirring time was 20 min. Moreover, the Cd(II) removal efficiency of nZVI@AC prepared by ILPR (nZVI@AC-I) was greater than 92.00%, which was superior to that of nZVI@AC prepared by TLPR (nZVI@AC-T). The characterization results showed that the pore parameters, surface functional groups and iron contents of nZVI@AC-I and nZVI@AC-T were basically the same. However, the distribution of iron-containing particles on the surface of nZVI@AC-I was more uniform. Furthermore, the Fe 0 in nZVI@AC-I had a smaller particle size and a higher content. Overall, this study provided a promising approach for nZVI@AC preparation. Graphical abstract: Image 1 Highlights: A liquid-phase reduction method using the solid reducing agent is proposed. This method successfully synthesized nano zero-valent iron/activated carbon . This method produced Fe 0 with smaller particle size and higher content. This method does not require the use of dispersants and ethanol. The material synthesized by this method exhibited a better removal rate of Cd(II).